2013
DOI: 10.3168/jds.2012-5441
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary proportion of grass silage on milk fat with emphasis on odd- and branched-chain fatty acids in dairy cows

Abstract: High proportions of forage in diets fed to dairy cows are interesting options in conventional production, and mandatory in organic dairy farming (e.g., within the European Union). The objectives of the present study were to study the milk fatty acid (FA) profiles, with particular focus on the odd- and branched-chain FA (OBCFA) and their association with diet composition, using 3 different proportions of grass silage in the diet. The OBCFA profiles in milk have been suggested to be potential markers to assess n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 22 publications
3
29
0
1
Order By: Relevance
“…The milk and meat from animals with a pasturebased diet reportedly have a better nutritional quality due to increased PUFAs in these products, mainly omega-3 and CLA cis-9 trans-11 (Patel et al 2013). This fact is directly associated with the high content of PUFA, mainly linolenic acid, in green forage (Dewhurst et al 2006); studies with temperate forages have shown that some pasture management strategies can increase its concentrations in plants (Glasser et al 2013, Witkowska et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The milk and meat from animals with a pasturebased diet reportedly have a better nutritional quality due to increased PUFAs in these products, mainly omega-3 and CLA cis-9 trans-11 (Patel et al 2013). This fact is directly associated with the high content of PUFA, mainly linolenic acid, in green forage (Dewhurst et al 2006); studies with temperate forages have shown that some pasture management strategies can increase its concentrations in plants (Glasser et al 2013, Witkowska et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Vlaeminck et al (2006) found similar results where iso C15:0 increased in proportion to grass silage. Another study by Patel et al (2013) also discovered that augmented proportions of grass silage in the diet increased the branched-chain FAs iso C15:0 and iso C17:0. …”
Section: Resultsmentioning
confidence: 99%
“…Higher concentrations of branched chain FA in milk are typically a result of high forage diets, due to a larger population of cellulolytic bacteria that can produce acetate (Patel et al, 2013). Acetate can be elongated into branched-chain FAs, which will eventually be deposited into the milk (Patel et al, 2013). In SARA, there are more amylolytic bacteria in the rumen, which produce propionate, leading to less branched-chain FAs being produced (Fievez et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations